A cislunar transportation system fueled by lunar resources. (August 2016) - Sowers, George F.
Abstract: A transportation system for a self sustaining economy in cislunar space is discussed. The system is based on liquid oxygen (LO2), liquid hydrogen (LH2) propulsion whose fuels are derived from ice mined at the polar regions of the Moon. The elements of the transportation system consist of the Advanced Cryogenic Evolved Stage (ACES) and the XEUS lander, both being developed by United Launch Alliance (ULA). The main propulsion elements and structures are common between ACES and XEUS. Both stages are fully reusable with refueling of their LO2/LH2 propellants. Utilization of lunar sourced propellants has the potential to dramatically lower the cost of transportation within the cislunar environs. These lower costs dramatically lower the barriers to entry of a number of promising cislunar based activities including space solar power. One early application of the architecture is providing lunar sourced propellant to refuel ACES for traditional spacecraft deployment missions. The business case for this application provides an economic framework for a potential lunar water mining operation.